Proceedings of the 1996 ACM Conference on Computer Supported Cooperative Work - CSCW '96 1996
DOI: 10.1145/240080.240295
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for addressing fundamental privacy and disruption tradeoffs in awareness support systems

Abstract: This paper describes a fundamental dual tradeoff that occurs in systems supporting awareness for distributed work groups, and presents several specific new techniques which illustrate good compromise points within this tradeoff space. This dual tradeoff is between privacy and awareness, and between awareness and disturbance. Simply stated, the more information about oneself that leaves your work area, the more potential for awareness of you exists for your colleagues. Unfortunately, this also represents the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
160
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(163 citation statements)
references
References 18 publications
0
160
1
2
Order By: Relevance
“…the eyes) or blurring or pixelation of faces [7,17,20,36] were eventually tested. However, these methods are visually intrusive and target human and algorithmic recognition alike.…”
Section: Related Workmentioning
confidence: 99%
“…the eyes) or blurring or pixelation of faces [7,17,20,36] were eventually tested. However, these methods are visually intrusive and target human and algorithmic recognition alike.…”
Section: Related Workmentioning
confidence: 99%
“…To make sure that it could be seen from further away than just in front of the monitor, the indicator was implemented as a traffic light, The traffic light would be green if the other household had their system turned on, otherwise red. In some situations, showing information about another household's activities in this way could be considered an invasion of privacy, albeit an inevitable one, because if "one person in the media space [is] to have richer awareness, others must necessarily have less privacy" (Hudson & Smith, 1996). However, since research on communication between distributed family members has found that in general privacy is something their participants "did not seem too concerned about" (Tee at el., 2009), this was not deemed a major issue here.…”
Section: Implemented Modificationsmentioning
confidence: 99%
“…Other techniques for filtering private video scenes have been developed recently: a low resolution image as in the Nynex Porthole (Lee, 1997), a ghost that denotes moving entities over time while blurring the entity itself (Hudson , 1996).…”
Section: Publication Filtermentioning
confidence: 99%